2022
DOI: 10.1039/d2cp01978g
|View full text |Cite
|
Sign up to set email alerts
|

Photochemically triggered cheletropic formation of cyclopropenone (c-C3H2O) from carbon monoxide and electronically excited acetylene

Abstract: Cyclopropenone is one of few organic molecules detected in interstellar molecular clouds to date. Its formation mechanism from carbon monoxide and photoexcited acetylene is investigated, giving key insight into its formation in extreme conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…PI-ReToF-MS is exploited to understand the formation pathways of complex organic molecules (COMs) within interstellar analogue ices. , This technique is utilized here to identify individual CH 2 SO isomers formed in irradiated CO–H 2 S ice based on their ionization energies. The PI-ReToF-MS data of the photoionized, desorbing molecules from the irradiated ices are compiled in Figure ; these raw data are required to extract TPD profiles of m/z = 62 at two photon energies of 10.82 and 10.39 eV (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…PI-ReToF-MS is exploited to understand the formation pathways of complex organic molecules (COMs) within interstellar analogue ices. , This technique is utilized here to identify individual CH 2 SO isomers formed in irradiated CO–H 2 S ice based on their ionization energies. The PI-ReToF-MS data of the photoionized, desorbing molecules from the irradiated ices are compiled in Figure ; these raw data are required to extract TPD profiles of m/z = 62 at two photon energies of 10.82 and 10.39 eV (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…The simplest one among these, cyclopropenylidene (CPD), ubiquitous in the ISM, has been recently explored theoretically to appraise its cooperativity, in terms of its tendency toward the formation of homologous molecular clusters and also with water . Cyclopropenone (HCCOCH, or c-C 3 H 2 O, herein abbreviated “CPN”), is another simple exotic carbene that possesses an intrinsic C 2v symmetry, which manifests in the Sagittarius B2 ( N ) region of the ISM. CPN has been theoretically, as well as experimentally investigated upon, along with its derivatives, over the past seven decades. In particular, CPN plays its role as a tracer in nonequilibrium chemistry when interstellar acetylene and carbon-monoxide ices react under a cosmic shower .…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the formation of 1 may involve the excited state photochemistry of low-lying electronic states of acetylene, which can be accessed by the kinetic energy of the impinging electrons during the irradiation. Recent studies have shown that excited states of acetylene play key roles in the formation of cyclopropenone ( c -C 3 H 2 O) and benzene (C 6 H 6 ) in interstellar acetylene-containing analog ices. ,, The excited acetylene molecule may react with the nearby acetylene molecule to form 1 via a concerted mechanism in low-temperature ices. The second pathway for the formation of 1 may involve vinylacetylene ( 7 ), which undergoes isomerization to form 1 via a barrier of 203 kJ mol –1 and a reaction energy of 140 kJ mol –1 .…”
mentioning
confidence: 99%